A Proposed Protocol for Ordinary and Extraordinary Hygienic Maintenance in Different Implant Prosthetic Scenarios - Pietro Felice; Angelica Bertacci; Lorenzo Bonifazi; Maryia Karaban; Luigi Canullo; Roberto Pistilli; Pasquale Sammartino; Roberta Gasparro; Carlo Barausse (Applied Sciences, 2021)
Prevention of peri-implantitis involves the early diagnosis of peri-implant mucositis. This article presents a protocol of hygienic maintenance in different implant prosthetic scenarios: single crown, fixed partial prosthesis, fixed full-arch, and overdentures. Others clinical conditions have to be taken into consideration: patient compliance; history of periodontitis; implants placed in augmented bone; short, zygomatic, pterygoid, and tilted implants; and complex prosthesis with false gingiva. Two levels of implant maintenance are described: ordinary, performed by dental hygienist, and extraordinary, carried out by both dentist and hygienist. Extraordinary maintenance also involves the removal and decontamination of the prosthetic structure. To obtain an effective prevention of peri-implantitis, one must plan ordinary and extraordinary hygiene in relation to the type of rehabilitation and clinical parameters.